Beta diversities of grassland birds indicate the importance of pastoralism for nature conservation of the Qinghai–Tibetan plateau - Li, Li; Tietze, Dieter Thomas; Fritz, Andreas; Basile, Marco; Lü, Zhi; Storch, Ilse (Frontiers in Conservation Science, 2022)
The post-2020 global biodiversity framework calls for a transformative change in food systems. Promoting agricultural multifunctionality is a viable approach to this sustainability transformation. The eastern Qinghai–Tibetan Plateau (QTP) is both one of the world’s largest livestock grazing systems and a hotspot of endemic birds in Asia. In this research, we aim to investigate the impact of livestock grazing on alpine bird assemblages at the local scale (alpha diversity) and their variation across the pastoral landscape (beta diversity). In the study area Nyanpo Yutse, we conducted surveys of 126 bird sample plots during two breeding seasons to acquire bird assemblage data. Meanwhile, we employed unmanned aerial vehicles to measure 2D and 3D habitat features within the 150-m radius. We investigated the key habitat variables driving the spatial distributions of both alpha and beta diversities of birds. Particularly, we partitioned beta diversity into its turnover and nestedness components and tested their patterns across sites of four levels of livestock grazing intensities (LGIs). Our results found no significant correlation between LGIs with species richness of birds, while 2D and 3D habitat complexity and built structure were positively correlated with alpha diversity (p < 0.05). At the landscape scale, pairwise LGI differences had no significant correlation (p > 0.05) with any pairwise beta diversity. The ordination plotting detected distinguished habitat preferences among 12 common birds and eight endemic birds. The multiple-site beta diversity of the 126 plots showed high species turnover (>0.871) where LGI was lower than 1.065 sheep units/ha, indicating the importance of moderate grazing for the conservation of diverse avian assemblages at the landscape scale. Our study demonstrated that extensive pastoralism is important for both maintaining the mosaic landscape and conserving avian biodiversity on the eastern QTP. We unveiled one of the ecological mechanisms through which synergies can be realized to support both agricultural production and biodiversity conservation in the Tibetan grazing system.